Extended treatment with selective phosphatidylinositol 3‐kinase and mTOR inhibitors has effects on metabolism, growth, behaviour and bone strength. (12th August 2013) - Smith, Greg C.; Ong, Wee‐Kiat; Costa, Jessica L.; Watson, Maureen; Cornish, Jillian; Grey, Andrew; Gamble, Greg D.; Dickinson, Michelle; Leung, Sophie; Rewcastle, Gordon W.; Han, Weiping; Shepherd, Peter R.
<x xml:space="preserve">Abstract</x> The class I phosphatidylinositol 3‐kinases (PtdIns3Ks) mediate the effects of many hormones and growth factors on a wide range of cellular processes, and activating mutations or gene amplifications of class I PtdIns3K isoforms are known to contribute to oncogenic processes in a range of tumours. Consequently, a number of small‐molecule PtdIns3K inhibitors are under development and in clinical trial. The central signalling role of PtdIns3K in many cellular processes suggests there will be on‐target side effects associated with the use of these agents. To gain insights into what these might be we investigated the effect of extended daily dosing of eight small‐molecule inhibitors of class Ia PtdIns3Ks. Animals were characterized in metabolic cages to analyse food intake, oxygen consumption and movement. Insulin tolerance and body composition were analysed at the end of the experiment, the latter using EchoMRI. Bone volume and strength was assessed by micro‐CT and three‐point bending, respectively. Surprisingly, after sustained dosing with pan‐PtdIns3K inhibitors and selective inhibitors of the p110α isoform there was a resolution of the impairments in insulin tolerance observed in drug‐naïve animals treated with the same drugs. However, pan‐PtdIns3K inhibitors and selective inhibitors of the p110α have deleterious effects on animal growth, animal behaviour and bone volume and strength. Together, these findings identify a range of on target effects of PtdIns3K inhibitors and suggest use of these drugs in humans may have important adverse effects on metabolism, body composition, behaviour and skeletal health.